The determinants of the exchange rate movement in Malaysia / Najlaa Zahirah Hossen - Hossen, Najlaa Zahirah (Faculty of Business and Management, 2015)
The changes in the economy development have given different effects to the foreign exchange rate in Malaysia (RM) in which the exchange rate influences the purchasing power of the imports and exports of goods. The persistent level of fluctuations in Ringgit Malaysia (RM) has cause of concern in income and the capital gain, as well as the exchange rates can affect the trading relationship between two nations. In order to gained the results of fluctuations of foreign exchange rate in Malaysia, this report is created to investigate about the factors that affect the exchange rate in Malaysia. Due to that the independent variables that are chosen to investigate this matter are the inflation rate, current account balance, lending rate and terms of trade and the dependent variable is the exchange rate of the Ringgit Malaysia. The total data that have been collected are thirty quarterly data that have been taken from the year 2007 to the year 2014. Multiple Linear Regression Model is employed in order to analyze about the relationship between the variables.